Total training volume and muscle soreness parameters performing agonist or antagonist foam rolling between sets - Santana, H. G.; Lara, B.; Canuto Almeida da Silva, F.; Medina Eiras, P.; Andrade Paz, G.; Willardson, J. M.; Miranda, H. (Sports, 2021)
Background: Foam rolling (FR) has become very popular in recent years; however, the practice of FR between sets of resistance training (RT) for the lower limbs needs further examination. Purpose: Therefore, the purpose of the present study was to examine the effect of FR for the agonists (quadriceps) and antagonists (hamstrings) between multiple sets of the leg extension on repetition maximum performance (RM), fatigue resistance index (FRI), and muscle soreness (MS). Study design: Quasi-experimental clinical trial. Methods: Twenty trained men participated in this study (30.35 ± 6.56 years, 1.77 ± 0.05 cm, 87.70 ± 7.6 kg) and attended seven sessions with 48 h between sessions, (one familiarization session; two 10-RM test and retest sessions; and four experimental sessions). The four experimental sessions were performed in random order and included: agonist foam rolling (AFR), antagonist foam rolling (ANTFR), agonist/antagonist foam rolling (A/ANTFR), and traditional control (TP, without foam rolling). All sessions consisted of three sets for maximal repetitions with a 10-RM load for the leg extension. In the AFR and ANTFR sessions, there was a 120 s rest interval between sets, during which FR was done for the agonists or antagonists, respectively. In the A/ANTFR protocol, there was a 120 s rest interval between sets, during which FR was done for the agonists and antagonists. In the traditional protocol (TP), there was a 120 s passive rest interval between sets. Results: Regarding the total training volume (TTV), significant differences were noted between sessions (F3,57 = 11.014; p = 0.0001). The AFR, ANTFR, and A/ANTFR sessions had significantly higher TTV versus the TP (p < 0.05). Regarding the FRI, significant differences were noted between sessions (F3,57 = 2917, p = 0.042). A significantly higher fatigue index was shown for the ANTFR and AFR sessions versus the TP (p < 0.05). Regarding the total number of repetitions, significant differences were noted between sessions (F3,57 = 11.086, p = 0.0001). The total number of repetitions was significantly higher in the A/ANTFR, ANTFR, and AFR versus the TP session (p < 0.05). MS was significantly lower in the A/ANTFR, ANTFR, and AFR sessions versus the TP session (p < 0.05). Conclusion: In conclusion, foam rolling between sets for the agonist or antagonist separately or in succession, resulted in greater neuromuscular performance and higher fatigue indices, as well as reducing the perception of acute muscle soreness.